2006
DOI: 10.3892/ijo.28.2.307
|View full text |Cite
|
Sign up to set email alerts
|

Expression of keratinocyte growth factor receptor correlates with expansive growth and early stage of gastric cancer

Abstract: Abstract. The keratinocyte growth factor receptor, also known as KGFR/FGFR2 IIIb, is mainly localized in epithelial cells, and participates in the proliferation of these cells. In contrast, a recent study has revealed that the overexpression of KGFR in salivary adenocarcinoma induces growth inhibition, cell differentiation and apoptosis. We attempted to clarify the expression and role of KGFR in normal and cancerous human gastric tissues and cancer cell lines. Reverse-transcription polymerase chain reaction an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 28 publications
(33 reference statements)
0
27
0
Order By: Relevance
“…In this study, we found that, in noncancerous esophageal tissues, KGFR is localized in the lower one-third of squamous epithelial cells and its localization is broader than that of Ki-67, a proliferating cell marker. In gastric and colorectal tissues, KGFR is localized in the luminal surface of epithelial cells, but Ki-67 is localized in the nuclei of ductal cells in the basal and parabasal regions (14,27). These findings suggest that KGFR plays important roles not only in epithelial cell proliferation in the GI tract, but also in cell differentiation.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…In this study, we found that, in noncancerous esophageal tissues, KGFR is localized in the lower one-third of squamous epithelial cells and its localization is broader than that of Ki-67, a proliferating cell marker. In gastric and colorectal tissues, KGFR is localized in the luminal surface of epithelial cells, but Ki-67 is localized in the nuclei of ductal cells in the basal and parabasal regions (14,27). These findings suggest that KGFR plays important roles not only in epithelial cell proliferation in the GI tract, but also in cell differentiation.…”
Section: Discussionmentioning
confidence: 72%
“…We previously reported the KGFR expression in cancer cell lines derived from the GI tract, including the esophagus, stomach and colon (14,27). Conventional gastric cancer cell lines expressed KGFR, but special types of gastric cancer cell line from metastatic foci of adenosquamous cells and α-fetoprotein-producing gastric cancer cells did not express KGFR (27,29).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…FGFR and FGF are often overexpressed in numerous cancers, and their expression correlates with poor prognosis (7)(8)(9)(10)(11)(12)(13). Activating mutations in the FGFR kinase domain have been found in several types of tumors including breast, bladder, gastric, prostate, colon, multiple myeloma, and non-small cell lung carcinoma (NSCLC; refs.…”
Section: Introductionmentioning
confidence: 99%